2020
DOI: 10.1093/neuros/nyaa179
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy Technique Predicts Outcome in Posterior Circulation Stroke—Insights from the STAR Collaboration

Abstract: BACKGROUND Randomized controlled trials evaluating mechanical thrombectomy (MT) for acute ischemic stroke predominantly studied anterior circulation patients. Both procedural and clinical predictors of outcome in posterior circulation patients have not been evaluated in large cohort studies. OBJECTIVE To investigate technical and clinical predictors of functional independence after posterior circulation MT while comparing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The first-pass devices included the stent retriever in 101 (28.6%) patients, aspiration catheter in 123 (34.8%) patients, combined approach in 103 (29.2%) patients, and other devices in 26 ( 7 ). Between the patients with anterior and posterior circulation occlusions, the door-to-picture time (17 [12][13][14][15][16][17][18][19][20][21][22][23][24] vs. 24 [30.8%] patients, respectively, p = 0.709) were not significantly different between the patients. The details of mRS at discharge in all patients and in those with anterior and posterior circulation occlusions are summarized in Fig.…”
Section: Treatment Time Course and Outcomementioning
confidence: 86%
See 3 more Smart Citations
“…The first-pass devices included the stent retriever in 101 (28.6%) patients, aspiration catheter in 123 (34.8%) patients, combined approach in 103 (29.2%) patients, and other devices in 26 ( 7 ). Between the patients with anterior and posterior circulation occlusions, the door-to-picture time (17 [12][13][14][15][16][17][18][19][20][21][22][23][24] vs. 24 [30.8%] patients, respectively, p = 0.709) were not significantly different between the patients. The details of mRS at discharge in all patients and in those with anterior and posterior circulation occlusions are summarized in Fig.…”
Section: Treatment Time Course and Outcomementioning
confidence: 86%
“…Higher NIHSS; more intracranial stenotic lesions; longer door-to-picture time, door-to-needle time, door-to-puncture time, and door-to-reperfusion time; fewer passes; and higher mortality were significantly different, while successful reperfusion and favorable outcome demonstrated no significant differences between the groups. Previous reports have demonstrated that male preponderance [ 24 ], younger age [ 24 , 37 ], higher NIHSS score [ 21 , 22 , 24 ], longer onset-to-puncture time [ 21 , 37 ], longer onset-to-reperfusion time [ 37 ], higher rate of futile reperfusion [ 25 ], lower tendency of favorable outcome [ 21 23 , 25 ], and higher mortality [ 22 , 23 , 25 ] were observed in patients with posterior circulation occlusion. In contrast, there have also been some studies that reported similar or lower NIHSS scores [ 37 , 38 ], lower rates of symptomatic hemorrhage [ 25 , 37 ], similar rates of favorable outcome [ 37 , 38 ], and similar mortality [ 24 , 37 , 38 ] between patients with anterior and those with posterior circulation occlusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct Aspiration First-Pass Technique (ADAPT) is associated with higher rates of functional independence after posterior circulation thrombectomy, compared to stent retriever or combined approach in large "real-world" retrospective study [122]. Metaanalysis suggested that for patients with acute basilar artery occlusion, first-line ADAPT might achieve higher and faster recanalization, comparable neurological improvement, and safety, compared with first-line stent retrievers [123].…”
Section: Aspiration Vs Stent Retrievermentioning
confidence: 99%